Boundary value problem for the four-dimensional Gellerstedt equation - Berdyshev, A.S.; Ryskan, A.R. (Bulletin of the Karaganda University. Mathematics Series, 2021)
In this work, the solvability of the problem with Neumann and Dirichlet boundary conditions for the Gellerstedt equation in four variables is investigated. The energy integral method is used to prove the uniqueness of the solution to the problem. In addition to it, formulas for differentiation, autotransformation, and decomposition of hypergeometric functions are applied. The solution is obtained explicitly and is expressed by Lauricella’s hypergeometric function.